2015
DOI: 10.3390/en8031584
|View full text |Cite
|
Sign up to set email alerts
|

Active Power Filtering Using the ZDPC Method under Unbalanced and Distorted Grid Voltage Conditions

Abstract: Abstract:In this paper, we propose a new Zero Direct Power Control (ZDPC) technique for active compensation of harmonics and reactive power, using shunt active power filter (SAPF), based on cancellation of instantaneous active and reactive power disturbances by comparison with their zero references. To separate harmonic and fundamental components of the line voltage and current a highly selective filter (HSF) has been used. Depending on the power errors and line voltage vector position, a switching table produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…To date, the conventional STF-pq theory algorithm still produces a non-sinusoidal reference current [7,40,42] and thus forces the SAPF to operate based on a direct current controlled (DCC) scheme [43][44][45]. From previous literature [45][46][47], it is revealed that the SAPF switching operation produces switching ripples which potentially degrade the THD value of the mitigated source current.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, the conventional STF-pq theory algorithm still produces a non-sinusoidal reference current [7,40,42] and thus forces the SAPF to operate based on a direct current controlled (DCC) scheme [43][44][45]. From previous literature [45][46][47], it is revealed that the SAPF switching operation produces switching ripples which potentially degrade the THD value of the mitigated source current.…”
Section: Introductionmentioning
confidence: 99%
“…Under non-sinusoidal source voltage conditions, source voltage in α-β domain can actually be decomposed into dc and ac components as follows: In order to deal with non-sinusoidal source voltage conditions, a self-tuning filter (STF) is commonly applied to process the source voltage so that dc components of the source voltage can be extracted, serving as reference voltage to ensure in-phase operation of SAPF with the designated power system. In [7,40,42], the transfer function of STF for source voltage processing (after performing Laplace transformation) can be summarized as follows:…”
Section: Conventional Self-tuning Filter-based Instantaneous Power (Smentioning
confidence: 99%
See 3 more Smart Citations